2018
DOI: 10.1039/c8cp05521a
|View full text |Cite
|
Sign up to set email alerts
|

Analysing thermophoretic transport of water for designing nanoscale-pumps

Abstract: The net flow of water through a thermal nanopump is linearly dependent on the imposed thermal gradient of the carbon nanotube, leading to controlled water transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Therefore, the obtained pressure difference across the membrane is calculated using the Equation S7 in SI. That type of non-equilibrium molecular dynamics simulations used to create a pressure gradient can also be applicable for thermal [48][49] and stiffness [50] gradients. Software details and modeling parameters are provided in Section S13 in SI.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…Therefore, the obtained pressure difference across the membrane is calculated using the Equation S7 in SI. That type of non-equilibrium molecular dynamics simulations used to create a pressure gradient can also be applicable for thermal [48][49] and stiffness [50] gradients. Software details and modeling parameters are provided in Section S13 in SI.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…Historically, the first experimental results on thermo-osmosis were published by Lippmann 9 and Aubert 10 at the beginning of the 20th century. Since then, a broad literature has been devoted to the study of aqueous solutions and various membranes, both from experiments [11][12][13][14][15] or molecular dynamics (MD) simulations [16][17][18][19][20] . Some disagreements have been reported for aqueous electrolytes, specifically in the flow direction (toward the hot side, so-called thermophilic flow, or toward the cold side, so-called thermophobic flow) for similar systems [21][22][23][24] , or on the relation between the flow amplitude and surface charge 13 .…”
Section: J O U R N a L Na Mementioning
confidence: 99%
“…Thermo-osmosis has seen a renewed interest due to the massive thermo-osmotic responses predicted by the use of novel materials, such as soft nanochannels 30 , carbon-nanotubes 5,18,31 or graphene 17 , together with novel experiments by Bregulla et al 24 , which first reported a microscale manifestation of thermo-osmotic flows. Thermo-osmotic flows could in particular be boosted by the slip boundary condition (BC), which describes the velocity jump v s at the interface by a general expression first proposed by Navier 32,33 :…”
Section: J O U R N a L Na Mementioning
confidence: 99%
“…Other models of pumps based on temperature gradient show comparable velocities at a micro sized pump. 6 High pumping rates (B1 m s À1 ) theoretically can be obtained with high temperature gradients (B20-100 K nm À1 ) at nano-sized pumps, 7,16 but such extreme gradients may be difficult to achieve in experiments.…”
Section: Resultsmentioning
confidence: 99%